«StressResponse» of the Organism During Oncosurgery Depending on Different Types of Anesthesia - A. O. Solovyev; V. T. Dolgikh; O. V. Leonov; O. V. Korpacheva (Общая реаниматология, 2016)
Objective: to investigate the severity of the stress response of the organism during surgery on the colon because of a tumor by determining the level of stress hormones and glucose depending on various types of anesthesia.Materials and methods. Patients who have undergone resection surgery because of the colon malignancy were divided into two groups: the study group (n=57) and comparison group (n=35). In the study group a multimodal anesthesia was performed that included a shallow sympathetic blockade in combination with surface inhalation anesthesia. In the comparison group inhalationintravenous anesthesia was performed on the basis of systemic administration of fentanyl when accompanied by myoplegia and sevoflurane insufflation. The levels of insulin, epinephrine, norepinephrine, dopamine, cortisol and glucose in serum were eavaluated during three periods of the study: prior to the induction of anesthesia, at the traumatic moment of operation and at the end of the surgery. Statistical hypothesis testing was performed using nonparametric methods and the data were processed with the aid of Statistica 6 software. Results. A significant increase of the level of cortisol and serum catecholamines was observed in comparison group during the 2nd and 3rd stages. In the study group, these indicators did not exceed standard values. Insulin level was higher in the study group during the 1st and 2nd stages compared to the comparison group. Insulin level at the end of the surgery was lower in the study group. The glycemic profiles were almost identical with hyper glycemia trend in the comparison group.Conclusion. Multimodal anesthesia provided most protective effect against stress during traumatic surgeries. The ratio of glucose and insulin values in groups demonstrate the capability of a multimodal anesthesia to prevent postoperative insulin resistance.